Influence of receipt drinking water excess ions copper and zinc on antioxidant-prooxidant balance in the liver conditions and mechanical injury and effectiveness of antidote therapy - O. Ye. Kopach; O. B. Svan; R. M. Boris (Kazimierz Wielki University, 2018)
In the late period of a traumatic illness (14-28 days), after intensive skeletal trauma infliction, elevated liver tissue is the intensity of free radical lipid oxidation, signs of extinction of antioxidant defense are noted. Against her background heavy skeletaltrauma and excessive intake of copper ions and zinc in comparison with animals without additional intoxication in these terms in liver tissue is higher level of lipid peroxidation, less - the activity of enzymes antioxidant protection. Introduction of unithiol to injured animals with excessive ions of copper and zinc within 14 days after application accompanied by severe skeletal trauma disorders significantly less traumatic disease markers studied as up to 28 days do not reach the level of animals without additional toxic effects